Legal Protection for Patients to Medical Procedures Performed By Young Dentist - Rahma Ariesti Lating; Wiwin Indriani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
Constitutes such a basic requirement of man, health so the need is will always to be fulfilled in order to improve the quality of human health, so as to be in his life quality will not cease to be guaranteed.To health services there are the relationship between individual patients, the doctor / medical workers and hospital sources said.The connections serve as a platform for arrangement on the health of the norms to protect patients in the form of health law norms and other like moral, of ethics, of decency, propriety and of order ( herkutanto, introductory law health, 1987.To protect patients from error and omission health services, in 1992 have enacted of act no 23 / 1992 on health and in 1999 have promulgation of the act no.8 / 1999 about consumer protection. The authority of the young doctor to perform the act of medical towards patients not been managed in a legal manner.In rsgmp just make a guidebook profession ( module ), which holds information about rule of action that may be undertaken by the young doctor, dental hospital by law, medical committee, having standard operating procedures they can manage the any action and doctors educator clinic as well as the young doctor were very well informed with responsibility for every one of them, Changing authority given doctor educator clinic to the young doctor administration of, only there has been no rules governing the involvement of in a book.